2008 Annual Review Dev Effectiveness : shared Global Challenges - World Bank (Independent Evaluation Group Studies, 2008)
For the World Bank and its partners, the ever-present test is to deliver results-to lift people out of poverty and promote socially and environmentally sustainable development. Achieving such success in any individual country is increasingly intertwined with making progress on shared global challenges. The 2008 Annual Review of Development Effectiveness, an independent evaluation, presents evidence on the Bank's efforts in two important and connected areas: tracking outcomes of Bank projects and country programs; and progress in fostering global public goods, such as protecting the earth's climate and preventing the spread of dangerous communicable diseases